The fabulous world of Faberge (New York A&E Television Network ; distributed by New Video Group, 1997)
Tells the complete story of the master jeweler's life, from his rise to international fame to his narrow escape from a Bolshevik firing squad. Jewelry experts explain why Faberge's rare eggs are still some of the most coveted art objects in the world.
VHS format.
Executive producers, Robb Weller and Gary H. Grossman; writer/producer, Sue Nadell.
Keywords: Fabergé, Peter Carl, 1846-1920.; Jeweler, Russian